FACTORS OF EXTERNAL MIGRATION OF THE KYRGYZ RURAL POPULATION (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
Kyrgyzstan has long been an agrarian region. About 2/3 of the total population lives in rural areas today. In turn, the reform of the agricultural sector, as an industry where the bulk of the population (70%) is concentrated, led to the deinstitutionalization of collective and state farms. These circumstances led to the formation of a contingent characterized as potential migrants. According to the author, the most significant factors in the external migration of rural youth are the desire to improve their educational level, as well as the desire of the rural population to change their financial and socio-economic status. Factors such as gender, age, marital status, education, language potential are also the main indicators for external migration.
Keywords: state, society, region, rural youth, external migration, factor, unemployment.